Perlakuan Terhadap Anak-Anak Indigenous People Dan Tanggung Jawab Negara - Margareta Rahalus; Josina Augustina Yvonne Wattimena; Irma Halimah Hanafi (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Indigenous peoples continue to face threats to their sovereignty, the sovereignty that is meant is centered on how the state positions indigenous peoples into national policies, by imposing values on indigenous peoples.Purposes of the Research: To examine and find out whether the treatment of Indigenous People's children in Canada violates the provisions of International Law and to find out how the state's responsibility for the human rights of Indigenous People's children is. Methods of the Research: This research is a normative juridical law research, with primary and secondary legal materials as a source of law by using the nature of prescriptive research that aims to obtain suggestions on what to do.Results of the Research: The results of the study show that the treatment of children of indigenous people in Canada violates the provisions of international law, where indigenous children receive treatment from the state in the form of violence or coercion which is contrary to human rights and fundamental freedoms regulated in the ILO (International Labor Organization) Conventions. UNDRIP Declaration (United Nation Declaration of Rights on the Indigenous Peoples), United Nations Convention on the Rights of the Child, then on the International Covenant on Civil and Political Rights) and also to the International Covenant on Economic, Social and Cultural Rights.